Growth Dynamics and Electron Reflectivity in Ultrathin Films of Chiral Heptahelicene on Metal (100) Surfaces Studied by Spin‐Polarized Low Energy Electron Microscopy. Issue 12 (15th December 2021) - Baljozović, Miloš; Fernandes Cauduro, André L.; Seibel, Johannes; Mairena, Anaïs; Grass, Stéphane; Lacour, Jérôme; Schmid, Andreas K.; Ernst, Karl-Heinz
Abstract : Helically shaped aromatic hydrocarbons, so‐called helicenes, provide promising properties for chiral organic electronics. A special transition from a dense first layer into a double layer, coexisting with a depleted first layer is observed with low‐energy electron microscopy. For further details, see article number 2100263 by Andreas K. Schmid, Karl‐Heinz Ernst and co‐workers (also presented within the article selection "60 years of pss").